DEVELOPMENT OF PROJECT-BASED LEARNING-BASED INTERACTIVE E-MODULES IN GRAPHIC DESIGN COURSES - Sarwandi Wandi; Dito Putro Utomo (Jurnal Scientia, 2022)
This e-module was developed based on problems that occur during the learning process, the teaching materials used are still not optimal and some materials are not following the characteristics of students and learning objectives. Students are also less active in participating in the learning process and cannot collaborate in solving a problem, so it is necessary to develop relevant and innovative Project-Based Learning-Based Interactive E-Modules to help students more easily understand learning materials, be active in the learning process, and improve independence in learning. The method used in this research is research and development (R&D) by adopting the 4D (Four-D) development model which includes 4 steps, namely: define, design, develop, and disseminate. By definition five activities must be carried out, namely: 1) Initial analysis, 2) Student analysis, 3) Task analysis, 4) Concept analysis and 5) Formulation of learning objectives. In the design four activities must be carried out, namely: 1) Preparation of test standards, 2) Selection of media, 3) Selection of formats, and 4) Initial design. In development two steps must be done, namely: 1) Expert assessment, and 2) Development trial. And the last is dissemination, this stage is the dissemination stage to promote the product developed so that it is accepted by users, individuals, groups, and systems. The results of the research and development of project-based learning-based interactive e-modules can be seen from the validity tests of both media and materials that have been carried out with an average media validity value of 0.86 (valid), and an average material validity value of 0.78 (valid).